Cholera. Issue 10333 (9th April 2022) - Kanungo, Suman; Azman, Andrew S; Ramamurthy, Thandavarayan; Deen, Jaqueline; Dutta, Shanta
Summary: Cholera was first described in the areas around the Bay of Bengal and spread globally, resulting in seven pandemics during the past two centuries. It is caused by toxigenic Vibrio cholerae O1 or O139 bacteria. Cholera is characterised by mild to potentially fatal acute watery diarrhoeal disease. Prompt rehydration therapy is the cornerstone of management. We present an overview of cholera and its pathogenesis, natural history, bacteriology, and epidemiology, while highlighting advances over the past 10 years in molecular epidemiology, immunology, and vaccine development and deployment. Since 2014, the Global Task Force on Cholera Control, a WHO coordinated network of partners, has been working with several countries to develop national cholera control strategies. The global roadmap for cholera control focuses on stopping transmission in cholera hotspots through vaccination and improved water, sanitation, and hygiene, with the aim to reduce cholera deaths by 90% and eliminate local transmission in at least 20 countries by 2030.